The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fimmu.2021.689181
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transforming Growth Factor-β1 in Regulating Fetal-Maternal Immune Tolerance in Normal and Pathological Pregnancy

Abstract: Transforming growth factor-β (TGF-β) is composed of three isoforms, TGF-β1, TGF-β2, and TGF-β3. TGF-β1 is a cytokine with multiple biological functions that has been studied extensively. It plays an important role in regulating the differentiation of immune cells and maintaining immune cell functions and immune homeostasis. Pregnancy is a carefully regulated process. Controlled invasion of trophoblasts, precise coordination of immune cells and cytokines, and crosstalk between trophoblasts and immune cells play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 115 publications
2
38
0
Order By: Relevance
“…Further, it also aids in angiogenesis, Treg production, balance between M1-M2 macrophage polarization and regulation of the NK cell function (Yang et al, 2021). In our study, we reported significantly increased (P < 0.05) mRNA expression of TGF-β1 in PBMCs of the pregnant cows.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Further, it also aids in angiogenesis, Treg production, balance between M1-M2 macrophage polarization and regulation of the NK cell function (Yang et al, 2021). In our study, we reported significantly increased (P < 0.05) mRNA expression of TGF-β1 in PBMCs of the pregnant cows.…”
Section: Discussionsupporting
confidence: 59%
“…The level of TGF-β1 has been reported to be higher in pregnant women, which revealed its potential regulatory function in fetal allograft survival in successful pregnancies (Ayatollahi et al, 2007). Further, it also aids in angiogenesis, Treg production, balance between M1-M2 macrophage polarization and regulation of the NK cell function (Yang et al, 2021). In our study, we reported significantly increased (P < 0.05) mRNA expression of TGF-β1 in PBMCs of the pregnant cows.…”
Section: Discussionmentioning
confidence: 99%
“…Both LAP TGF-b1 and TGF-b have well-known immunosuppressive properties (37,38). TGF-b is a main inducer of Treg cell development and function, which are key elements in the immune modulation of both MS and pregnancy (39,40). However, since active TGF-b1 is difficult to measure, it is not optimal as a biomarker, and its broad biological effects complicate its use in treatment (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreovere, an increase in TGF-β is observed, which is essential for the transition between the cell-mediated immune response to the humoral one [ 39 ]. In addition, there is an increase in HBD1 and HBD4, which is extremely interesting since the first is constitutively expressed in the genital tract [ 40 , 41 ], while the second is inducible in case of infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%